Structure and morphology of nano-sized W-Ti/Si thin films - Petrović Suzana M.; Adnađević Borivoje; Peruško Davor; Popović Nada; Bundaleski Nenad; Radović Milan; Gaković Biljana; Rakočević Zlatko (Journal of the Serbian Chemical Society, 2006)
Thin films were deposited by d.c. sputtering onto a silicon substrate. The influence of the W-Ti thin film thickness to its structural and morphological characteristics of a nano-scale were studied. The phase composition and grain size were studied by X-ray diffraction (XRD), while the surface morphology and surface roughness were determined by scanning tunneling microscopy (STM). The analysis of the phase composition show that the thin films had a polycrystalline structure - they were composed of a b.c.c. W phase with the presence of a h.c.p. Ti phase. The XRD peak in the scattering angle interval of 38º-43º was interpreted as an overlap of peaks corresponding to the W(110) and Ti(101) planes. The grain size and the mean surface roughness both increase with the thikness of the thin film. The chemical composition of the thin film surface was also analyzed by low energy ions scattering (LEIS). The results show the surface segregation of titanium, as well as a substantial presence of oxygen an the surface.